Influence of hydroxyapatite particle size on the flowability of PLA/HA filament / Nur Munirah Mustaza ... [et al.] - Mustaza, Nur Munirah; Mohd Salleh, Farrahshaida; Rahmat, Syahmin Ilyana; Marzuki, Afeeqa Puteri; Izdihar Tharazi, Izdihar Tharazi; Ismaill, Muhammad Hussain; Murat, Bibi Intan Suraya (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Advanced bioactive ceramic materials, Hydroxyapatite (HA) and Polylactic Acid (PLA) are common in bone regeneration implants. As demand for customised implant products increases, research increasingly focuses on developing composite filament manufacturing technology. However, creating PLA/HA composite filament faces challenges, including clumping HA particles and uneven flowability. The brittleness of the filament properties makes it unsuitable for Fused Deposition Modelling (FDM) printing, causing inconsistent extrusion and reduced filament strength. The purpose of this study is to compare the effectiveness of microHAs (m-HAs) and nanoHAs (n-HAs) in the production of filament composite fibers, based on the flowability assessment. The particle size of the micro-HA was reduced to nano by a ball mill process using 4 mL ethanol and the ball-powder ratio of 5:1, which was verified by the particle size analyzer. The feedstock comprises 79.5 wt.% PLA, 19.5 wt.% HA and 1 wt.% impact modifier (IMK) was mixed and rheological tested (130 ℃ to 150 ℃, shear rate: 20-1000 s-1) to achieve pseudoplastic behaviour (n<1). The rheological tests showed that both feedstocks exhibited pseudoplastic behaviour (n<1) across all temperatures studied. The properties of the feedstock were observed by scanning electron microscopy (SEM), and tensile tests evaluated the filament strength. The investigation found that nano-sized HA filament has 24% higher strength than micro-sized PLA/HA filament.